(untitled) (Journal of Pharmaceutical Negative Results, 2022)
The aim of the study is to investigate oxidative stress in sheep infected with hydatid cyst by determining the activities of Total antioxidants (TAOS) and Malonaldehyde (MDA) and their relationship in liver tissues. Fifteen infected livers and 15 healthy livers were included in the present study. The levels of TAOS and MDA in homogenized liver tissue and in parasite tissue were measured using ELISA. The findings of the study revealed that high levels of MDA were found in infected livers compared to healthy livers (P value <0.05) and low levels of TAOS were found compared to healthy livers. Pearson correlation coefficient between MDA and TAOS was inversely negative. The study comes to a conclusion that there is a relationship between TAOS antioxidants and MDA oxidants in the parasite and their role in oxidative stress in sheep livers.